Developing a Value-Based Moderate Islamic Education Model: A Case Study of Pesantren Sidogiri Pasuruan - Purwowidodo, Agus; Zaini, Muhamad (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
Islamic boarding schools, known as pondok pesantren, are the oldest and indigenous Islamic educational institutions in Indonesia. Islamic education has been a tradition passed down through generations. This study focuses on the Islamic education model at Sidogiri Pasuruan Islamic Boarding School using a qualitative approach, specifically a narrow but in-depth case study. Data were obtained from key informants through in-depth interviews, participatory observations, and document studies. Data analysis in this research used content analysis. The findings of this study are as follows: First, the Islamic education at Sidogiri Islamic Boarding School is traditional. However, it is also characterized by moderate Islamic education. Second, the moderation in Islamic education at Sidogiri is achieved through the inculcation and internalization of values to the students by the kyai (Islamic scholars). These intangible values have a significant impact on shaping the students’ character, including values of sincerity, devotion, manners, the spirit of compliance, and the value of struggle. Despite the integration of technology into daily activities and the adoption of extremist references, students maintain their steadfastness in their values and critically filter these references. Third, the Islamic education model implemented is a critical integrative model, combining classical education methods like sorogan and bandongan with modern educational methods, including the use of artificial intelligence. This approach produces students with critical yet ethical personalities.